Efficacy of passive immunization in broiler chicks via an inactivated Escherichia coli autogenous vaccine administered to broiler breeder hens. Issue 5 (3rd September 2022) - Keita, Alassane; Le Devendec, Laetitia; Amelot, Michel; Puterflam, Julie; Lucas, Camille; Bougeard, Stéphanie; Delannoy, Sabine; Schouler, Catherine; Fach, Patrick; Lucas, Pierrick; Souillard, Rozenn; Kempf, Isabelle
ABSTRACT: Avian pathogenic Escherichia coli (APEC) cause extra-intestinal infections called colibacillosis, which is the dominant bacterial disease in broilers. To date, given the diversity of APEC strains and the need for an acceptable level of protection in day-old chicks, no satisfactory commercial vaccine is available. As part of a French nationwide project, we selected three representative strains among several hundred APEC that cause colibacillosis disease. We first performed experiments to develop colibacillosis in vivo models, using an inoculum of 3 × 10 7 CFU of each E. coli strain per chick. Two APEC strains (19-381 and 19-383-M1) were found to be highly virulent for day-old chicks, whereas the third strain (19-385-M1) induced no mortality nor morbidity. We then produced an autogenous vaccine using the (Llyod, 1982; MaCQueen, 1967) 19–381 and 19-383-M1 APEC strains and a passive immunization trial was undertaken. Specific-pathogen-free Leghorn hens were vaccinated twice 2 weeks apart, the control group receiving a saline solution. The vaccinated and control hens exhibited no clinical signs, and egg production and fertility of both groups were similar. Fertile eggs were collected for 2 weeks after the second vaccination and chicks were obtained. After challenge with each APEC (19-381 and 19-383-M1), chicks appeared to be partially protected from infection with the 19-383-M1 strain, with 40% mortality compared with 80% for the non-vaccinated chicks. No protection was found when the chicks were challenged with the 19–381 strain. Now, further work is needed to consider some aspects: severity of the pathogen challenge model, persistence of the protection, number of APEC strains in the autogenous vaccine, choice of adjuvants, and heterologous protection by the vaccine made from strain 19-383-M1. RESEARCH HIGHLIGHTS Three APEC strains were characterized and selected to develop in vivo models of colibacillosis. A bivalent autogenous vaccine was produced and a passive immunization trial was carried out. Protection of chicks was demonstrated when challenged with the 19-383-M1 APEC strain (homologous challenge). Further work is needed in particular to evaluate the protection against heterologous challenge.